Effect of Manipulating Advanced Kinematic Information on Hitting Movement Prediction, Perception, and Action. Issue 4 (2nd October 2021) - Takamido, Ryota; Yokoyama, Keiko; Yamamoto, Yuji
ABSTRACT: Purpose : This study examined the effect of manipulating advanced kinematic information about opponents' pitching movement on ball speed prediction, ball speed perception, and impact timing errors under strict temporal constraints (i.e., a softball game). Method : Three experiments were conducted using visual stimuli consisting of varied kinematic information—different pitching movements with the same ball trajectory. In Experiment 1, participants observed the pitching movement of the visual stimuli and predicted pitched ball speed as a two-interval forced choice discrimination task (2IFC). In Experiment 2, participants observed both the pitching movement and ball trajectory, and evaluated the pitched ball speed as a 2IFC. In Experiments 3a and 3b, they tried to swing against the pitched ball presented on the screen as accurately as possible with regard to timing. Results : Batters tended to predict the ball was moving faster when the pitching movement was faster (Experiment 1). Incorrectly predicting the ball speed due to the difference in advanced kinematic information also biased batters' perception of the speed (Experiment 2), and this biased prediction yielded congruent impact timing (Experiment 3a). The impact timing error of naive participants also was affected by kinematic information (Experiment 3b). Conclusion : Limitations of this study (representative task design, sample size, and experimental procedures) notwithstanding, results indicate that, under strict temporal constraints, batters' perceptions and actions are sensitive to advanced kinematic information, which could lead to biased perceptions and actions.